Hanseníase em idosos: Aspectos clínicos, epidemiológicos e operacionais dos casos notificados em São Luís- Ma - OLIVEIRA, Eudijessica Melo de (2023)
Introduction: leprosy is a chronic disease caused by the bacillus Mycobacterium leprae, which can affect people of both sexes and of any age. However, by affecting the elderly population that is already naturally affected by the physiological changes of aging, leprosy has a direct influence on the functional decline of these people due to its disabling character. Objective: To analyze clinical, epidemiological and operational aspects of leprosy cases in the elderly. Methodology: descriptive, retrospective and evaluative study, carried out in São Luís, Maranhão, with cases of leprosy in the elderly notified in the National System of Notifiable Diseases SINAN- by the municipality, from 2015 to 2019. The population consisted of all cases of leprosy in elderly. Data collection was carried out between March and April 2023 with analysis in the Epi InfoTM software, version 7.2, based on descriptive statistics, and calculation of indicators for monitoring the progress of eliminating leprosy as a public health problem, and for assessing the quality of leprosy services: annual detection rate of new leprosy cases per 100,000 inhabitants; proportion of leprosy cases with grade 2 physical disability at diagnosis among new cases detected and assessed in the year, and proportion of new leprosy cases with grade of physical disability assessed at diagnosis. Results: from 2015 to 2019, 904 cases of leprosy in the elderly were reported. Most were male (54.65%), aged between 60 and 69 years (59.51%), brown (67.37%) and with 1st to 4th elementary school education (26.04%). The multibacillary operational classification was the most prevalent (90.27%), and the borderline clinical form (69.14%). Regarding the mode of entry, the highest frequency was new cases (82.08%). As for the degree of physical disability (GIF) at the time of diagnosis, 381(42.29%) had GIF1. The detection rate of new cases was high in 2017 (11.1%) and 2018 (10.0%) and in the indicator proportion of new cases with GIF2 at the time of diagnosis, the result was high in 2017 and medium in the other years evaluated. As for the proportion of new cases with GIF at the time of diagnosis, the result was good, with a proportion of evaluations above 90% in all years. Conclusion: the higher frequency of multibacillary leprosy cases in the elderly and the high percentage of cases with physical disabilities at the time of diagnosis suggests late diagnosis of the disease in the elderly. Indicators for monitoring the progress of eliminating leprosy as a public health problem revealed that there is a significant number of elderly people falling ill with leprosy and difficulty in early detection of cases, although the indicator that evaluates the quality of services has shown improvement in the provision of actions and services provided.